Сучасна правова парадигма інформаційної безпеки України - Банк, Р.; Bank, R. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Cтаття присвячена проблемі правового забезпечення інформаційної безпеки як складової національної безпеки України. Визначено нормативно-правове закріплення інформаційної безпеки України та окреслено суттєві прогалини в законодавстві України в регулюванні цього явища. Проведено аналіз та класифікацію видів інформаційних загроз. Запропоновані деякі шляхи вирішення проблеми правового забезпечення інформаційної безпеки у контексті збереження інформаційного суверенітету України. The article deals with the problem of legal support of the information security as an integral part of the national security of Ukraine. The concept of information has evolved from the intangible benefits matter into a financial dividend. Under such circumstances the protection of information and information resources is the primary task of the governmental institutions which are obliged to develop a mechanism of protecting information security.To neutralize the threat to the information resources there exists an integrated system of measures ensuring information security, which aims at counteracting the destabilizing factors that negatively influence the information environment. Now the information security plays a principal role in providing vital interests of the society, which is due to a significant increasein the influence of the information sphere on the life of society. The fact that priority of information security as the function of the state is fixed in the Constitution of Ukraine shows the level of importance of information processes and the importance of counteraction to the threats concerning it. Implementation of strategic objectives, basic principles of state information policy and restoring information sovereignty of Ukraine require improvements in the institutional and legal mechanisms to ensure information security, appropriate intellectual and innovative resources, including improvement of legislation in this field.
Modern Legal Paradigm of Information Security in Ukraine
Keywords: безпека; інформаційна безпека; національні інтереси; інформаційний суверенітет; безпекознавство; security; information security; national interests; information sovereignty